Eksplorasi Peran Tim Pendamping Keluarga (TPK) dalam Rangka Akselerasi Penurunan Stunting di Kabupaten Malaka - Maria Paula Marla Nahak; Yusfina Modesta Rua (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Stunting is a major health issue in Indonesia. In order to accelerate stunting reduction, the Indonesian government has mandated the formation of Family Assistance Team (FAT) at every village to assist stunting-risk families. FAT is the spearhead of stunting reduction at village level. Therefore, exploration of the role of FAT is a must to accelerate stunting reduction in Malaka Regency. This study aimed to explore the role of FAT in Malaka Regency. This was a qualitative study, with case study approach, conducted in 2 villages of stunting focus location in Malaka Regency, Nusa Tenggara Province, Indonesia from July to September 2023. A total of 12 informants were selected for this study by purposive sampling. Data collected by a set of interview guide. Data analyzed by thematic analysis and qualitative data validate by member check and theoretical triangulation. Thematic analysis revealed three main themes: (1) TPK Activities, encompassing both core activities and collaborative efforts; (2) Supporting Factors, which include both monetary and non-monetary incentives; and (3) Inhibiting Factors, which consist of budget limitations, lack of awareness, inadequate facilities, insufficient monitoring, and limited understanding of stunting. Regular monitoring needs to be carried out to ensure the implementation of TPK at village level.